Age and Reason of First Dental Visit among 0-14 years Old Children visiting Tertiary Care Center in Koshi Province - Bhagat, Tarakant; Shrestha, Ashish; Kumari Agrawal, Santosh; Dali, Mamta; Ojha, Ashma (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Introduction: The first dental visit should occur within 1 year of child’s age. Majority of parents bring their children for first dental visit only when there is a dental problem. Objective: This study was conducted to determine age and reason of first dental visit and to assess parents’ knowledge and attitude towards the first dental visit of the child. Methods: A cross sectional questionnaire-based study was conducted among 425 parents of children aged 0-14 years visiting the dental outpatient department. Each parent was interviewed by a single examiner. Descriptive statistics and Chi square test were used to report the data. The level of significance was set at p<0.05. Results: The mean age of the children at their first dental visit was 7.75±3.01 years, majority of them (37.4%) being at 7 to 9 years of age. Only few children (0.9%) reported for their first dental visit within 1 year of their age. Most common reasons of first dental visit were dental caries (43.1%) followed by pain (19.5%). Very few parents (18.6%) had knowledge on ideal age of the first dental visit. A statistically significant association was found between age and reason of the first dental visit (p<0.01). Conclusion: The findings of this study concluded that majority of the parents sought first dental visit of their children at older age especially when they had pain and dental caries. It reflects a need to improve parents’ knowledge on ideal age of the first dental visit for their children.